The Presence of Mycobacterial Antigens in Sarcoidosis Associated Granulomas - Shamaei, Masoud; Pourabdollah, Mihan; Mousaei, Hamed; Mirsaeidi, Mehdi; Masjedi, Mohamad Reza (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Sarcoidosis is a multi-organ disorder with unknown etiology.  The role of bacteria in pathogenesis of sarcoidosis is still controversial. This study analyses new aspects of Mycobacterium Tuberculosis (MTB) presence in sarcoidosis diseases. Objectives: To find MTB in paraffin embedded tissues of sarcoidosis patients, samples of 10 sarcoidosis, 12 confirmed pulmonary tuberculosis (PTB) and 5 controls associated with granulomatous tissues were analysed. Methods: The paraffin embedded tissue specimens of the selected patients from the pathology archive of a subspecialty pulmonary hospital in IRAN were evaluated by Real Time PCR for MTB DNA using IS6110. Immunohistochemistry (IHC) method using MTB purified protein derivative (PPD) antibody was used to detect mycobacterial antigens. Results: All sarcoidosis patients had negative MTB DNA results in Real time PCR analysis. This analysis resulted in 10 (83.3%) positive cases for TB patients. The IHC analysis for MTB anti-PPD antibody showed positive diffused cytoplasmic staining for all TB patients whereas this staining was positive for 3 sarcoidosis patients (30%). Conclusion: Amplification of the IS6110 DNA sequence that is the most common target used for MTB diagnosis is not sensitive method to detect MTB in sarcoidosis granuloma. However, tissue IHC for anti-PPD antibody shows higher performance to detect MTB in sarcoidal granulomas reveals a mycobacterial signature in sarcoidosis tissue with negative IS6110 assay. This finding supports Mycobacterium tuberculosis may have an etiologic role in sarcoidosis.